FASILITAS PUBLIK DAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PENUMPANG DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Wahyuni, Yuyun; Fadhil, Ridho Muhammad Zaidan; Dermawan, Arief (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Airports have a role as economic gateways, places to change modes of transportation, opening regional isolation and so on. Yogyakarta International Airport is an airport built in Kulon Progo Regency, Yogyakarta Special Region, which has a land area of ​​600 hectares and can accommodate up to 20 million passengers. In 2022, the total number of departing and arriving passengers at Yogyakarta international airport will be 2,885,460 people. The objectives of this research are: (i) To determine the significance of the influence of public facilities on passenger satisfaction at Yogyakarta International Airport; (ii) To determine the significance of the influence of service quality on passenger satisfaction at Yogyakarta International Airport The type of research used is quantitative research with descriptive methods. The samples taken were 140 people. The independent variables used are public facilities (X1) and service quality (X2) while the dependent variable is passenger satisfaction (Y). There are six indicators of public facilities, namely spatial planning, room planning, equipment/furniture, lighting and color, messages conveyed graphically and supporting elements. Service quality has five indicators, namely Reliability, Responsiveness, Assurance, Empathy and Tangibles. Meanwhile, to measure customer satisfaction using indicators of conformity to expectations, interest in revisiting and recommending. The instrument test tool uses validity and reliability tests. The analysis tool uses multiple linear regression tests, while hypothesis testing uses the t test and F test. To determine the contribution of variables, use the R2 test. The research results show that the two independent variables, namely public facilities and service quality, have a significant effect on passenger satisfaction at Yogyakarta International Airport. Both variables contribute 68.5% to passenger satisfaction.